Characterization of the permittivity of controlled porous water ice‐dust mixtures to support the radar exploration of icy bodies. Issue 12 (20th December 2016) - Brouet, Y.; Neves, L.; Sabouroux, P.; Levasseur‐Regourd, A. C.; Poch, O.; Encrenaz, P.; Pommerol, A.; Thomas, N.; Kofman, W.
Abstract: The internal properties of porous and icy bodies in the solar system can be investigated by ground‐penetrating radars (GPRs), like the COmet Nucleus Sounding Experiment by Radiowave Transmission instrument on board the Rosetta spacecraft which has sounded the interior of the nucleus of comet 67P/Churyumov‐Gerasimenko. Accurate constraints on the permittivity of icy media are needed for the interpretation of the data. We report novel permittivity measurements performed on water ice samples and icy mixtures with porosities in the 31–91% range. The measurements have been performed between 50 MHz and 2 GHz with a coaxial cell on a total of 38 samples with a good reproducibility. We used controlled procedures to produce fine‐grained and coarse‐grained ice samples with a mean diameter of 4.5 μm and 67 μm, respectively, and to prepare icy mixtures. The JSC‐1A lunar regolith simulant was used as the dust component in the mixtures. The results are focused on the real‐part ε ′ of the permittivity, which constrains the phase velocity of the radio waves in low‐loss media. The values of ε ′ show a nondispersive behavior and are within the range of 1.1 to 2.7. They decrease with the increasing porosity Φ according to E (1 − Φ ), with E equal to about 3.13 for pure water ice, and in the 3.8–7.5 range for ice‐dust mixtures with a dust‐to‐ice volumetric ratio in the 0.1–2.8 range, respectively. These measurements are also relevant for radiometers operating in the millimeter‐submillimeter domains, as suggested by the nondispersive behavior of the mixtures and of the pure components. Key Points: We report permittivity measurements between 50 MHz and 2 GHz of porous water ice and ice‐dust mixtures with porosities between 31% and 91% The porosity and the dust content dependencies of the real part of the permittivity, which is found to be nondispersive, are determined New constraints on the radio waves propagation in porous and icy media, as cometary nuclei, are provided by these measurements